Physical mechanisms encoded in photoionization yield from IR+XUV setups - Brabec, Thomas; Dinh, Phuong Mai; Gao, Congzhang; McDonald, Chris; Reinhard, Paul-Gerhard; Suraud, Éric (European Physical Journal D, 2019)
Abstract: We theoretically examine how and to which extent physical processes can be retrieved from two-color pump-probe experiments of atomic and molecular gases driven by an attosecond XUV pulse train and an infrared (IR) pulse. The He atom, the N2 molecule and Na clusters are investigated with time-dependent density functional theory. Results are interpreted on the basis of a simple model system. We consider observables most commonly used in experiments: ionization yield, photo-electron spectra, and angular distributions. We find that the basic time-dependent signatures are dominated by the interplay of IR laser and continuum electrons. System information, contained in the signal, will in general require careful disentangling from the effects of photon-electron dynamics. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-10-29